CHILEAN INFLUENCE IN FREIRE'S THOUGHT - Nicolò Valenzano (Universidade Federal de Juiz de Fora, 2021)
The years Paulo Freire spent in Chile were important for both the country and for Brazilian pedagogists; his influence on educational policies and practices is indubitable. In this article, however, I analyze the ways in which his time in Chile changed Freire's pedagogical ideas. Specifically, the Chilean context and the people he met there brought about a significant change in his conceptual framework and analytical tools, at least regarding two interlinked key points: heterodox Marxism and the idea of literacy. Marxist influence develops mainly as Marxist humanism and therefore involves the anthropological premise of Freirean pedagogy; in this reflection, the notion of praxis assumes a central role. The idea of literacy, as defined in the Chilean period, is at the forefront of the international debate on adult education.